1998
DOI: 10.1021/es970754m
|View full text |Cite
|
Sign up to set email alerts
|

Three-Compartment Model for Contaminant Accumulation by Semipermeable Membrane Devices

Abstract: Passive sampling of dissolved hydrophobic contaminants with lipid (triolein)-containing semipermeable membrane devices (SPMDs) has been gaining acceptance for environmental monitoring. Understanding of the accumulation process has employed a simple polymer film-control model of uptake by the polymer-enclosed lipid, while aqueous film control has been only briefly discussed. A more complete three-compartment model incorporating both aqueous film (turbulent-diffusive) and polymer film (diffusive) mass transfer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 9 publications
(16 reference statements)
7
98
0
1
Order By: Relevance
“…Both processes are related to the lipophilicity of the compound. In the work of Gale [26], three-compartment model was used for evaluating contaminant accumulation by triolein-SPMD. The model predicts aqueous film control for compounds with moderate to high K ow ; rather than polymer film control.…”
Section: Uptake Kineticsmentioning
confidence: 99%
“…Both processes are related to the lipophilicity of the compound. In the work of Gale [26], three-compartment model was used for evaluating contaminant accumulation by triolein-SPMD. The model predicts aqueous film control for compounds with moderate to high K ow ; rather than polymer film control.…”
Section: Uptake Kineticsmentioning
confidence: 99%
“…It is evident from Figure 5 that the sampler begins accumulating contaminant at the same time as the ambient pulse begins. There is no lag time for commencement of accumulation in this treatment, but one is likely to be observed in actual deployments [1,24]. This is a result of consideration of the sampler as a relatively simple single compartment or phase.…”
Section: Contamination Event or Pulsementioning
confidence: 99%
“…(1)- (3) is also based on the assumption that the chemicals accumulated by triolein-SPMDs are only in the triolein phase. However, the membrane is a functional constituent in the sampling process rather than simply a container for the triolein (Huckins et al, 1990a;Petty et al, 1994;Gale, 1998;Booij et al, 1998). Studies have indicated that the polyethylene membrane used in triolein-SPMD is a significant reservoir for hydrophobic residues and has a membrane/solute partitioning coefficients only a little less than the inner triolein reservoir (K pw : 0.1-0.5K tw , Gale, 1998).…”
Section: Models For Estimation Of Ambient Concentrationmentioning
confidence: 99%
“…However, the membrane is a functional constituent in the sampling process rather than simply a container for the triolein (Huckins et al, 1990a;Petty et al, 1994;Gale, 1998;Booij et al, 1998). Studies have indicated that the polyethylene membrane used in triolein-SPMD is a significant reservoir for hydrophobic residues and has a membrane/solute partitioning coefficients only a little less than the inner triolein reservoir (K pw : 0.1-0.5K tw , Gale, 1998). For example, a typical sampler has a total mass of about 4.5 g, which contains 0.91 g (1 ml) of triolein and represents a polyethylene to triolein ratio of about 4:1 (Huckins et al, 1996).…”
Section: Models For Estimation Of Ambient Concentrationmentioning
confidence: 99%
See 1 more Smart Citation